Sociocultural and Systemic Barriers to Parental Engagement in Pediatric Healthcare Decisions: A Qualitative Study - Ningrum, Luh De Kusuma (Sinergi International Journal of Psychology, 2024)
Parental involvement in pediatric healthcare decision-making plays a crucial role in shaping child health outcomes. This study explores the impact of communication, emotional support, and systemic factors on parental engagement, drawing from a comprehensive literature review. A systematic search was conducted using databases such as PubMed, Scopus, and Google Scholar, with specific inclusion and exclusion criteria to identify relevant studies. The results reveal that effective communication between parents and healthcare providers significantly enhances parental confidence and participation. Emotional stress and sociocultural dynamics, however, present substantial barriers to decision-making. Findings indicate that while structured family-centered care models have been effective in high-resource settings, parents in low-resource environments often face systemic inequities limiting their ability to engage fully in medical decisions. To address these barriers, policy interventions must promote inclusive and culturally sensitive healthcare frameworks that facilitate shared decision-making. Training programs for healthcare professionals should incorporate strategies to improve parent-provider communication and support parental mental health during high-stress medical scenarios. Future research should focus on evaluating the long-term impact of parental involvement and exploring technological interventions to bridge gaps in healthcare accessibility. By fostering stronger partnerships between parents and healthcare systems, this study underscores the importance of parental engagement in achieving improved pediatric health outcomes and ensuring equitable healthcare access.